THE EFFECT OF ONLINE GAMES AS A MEDIUM TO STUDENTS’ SPEAKING SKILL - Wirawati, Nur; Jabu, Baso; Aeni, Nur (Universitas Negeri Makassar, 2022)
This study aims to determine the effect of online games as a medium on speaking skills. These 4 fundamental English skills are speaking, listening, reading, and writing. The majority of people prefer speaking as their primary mode of communication. In Indonesia, English is a foreign language limited to classroom learning and is rarely used in everyday life, especially in speaking. So, some students need help with mastering English in speaking. Many students nowadays like playing online games as a hobby because Online Games have a worldwide server, so they can communicate with others using English. Online games have good and bad effects on learning, particularly when learning a new language. Most use online games as learning techniques and a friendly approach to learning English. This quantitative research uses a sample of 30 students at the language and literature faculty of Makassar State University. Data collection in this study used a questionnaire distributed by purposive sampling technique. The data were analyzed using simple linear regression (F-Test) and descriptive statistical analysis techniques. The results showed that the influence of online games on students' speaking ability had an effect of 43.4%. It can also be seen that the average student playing time is 2 hours, with the type of game most often played being FPS (First Person Shooter). Keywords — Effect, Online Game, Speaking Skill.